FOOD INTAKE AS A DETERMINANT OF NUTRITIONAL STATUS IN CARAT VILLAGE - Aprilya Tunggo Dewi; aprilya (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Introduction: The nutritional needs of children under five are increasing because they are in a phase of rapid growth and high physical activity. SSGI data for 2022 shows that in Pasuruan District in 2022, stunting reached 20.5%, wasting reached 12.4%, underweight reached 21.4%, and overweight reached 6.2%. One of the direct contributing factors to stunting is insufficient nutrient intake. Methods: The type of research applied was quantitative analysis with a cross-sectional design. The study period was from September 30 to October 05, 2024, with a population of 339 children under five. Sampling was done by purposive sampling, so that 75 toddlers were obtained. The process of collecting food consumption data was carried out using a food record form for 1x24 hours, and evaluating the nutritional status of toddlers using the BB / U index. Data analysis using the Chi-Square test to analyze the relationship between carbohydrate, protein, and fat intake with nutritional status. Results: This study shows that there are 24 respondents (23%) of toddlers with abnormal nutritional status characteristics and 51 respondents (68%) with normal nutritional status. The number of respondents who had sufficient carbohydrate intake was 58 people (77.3%), for sufficient protein intake, there were 46 respondents (61.3%), and the number of respondents with sufficient fat intake was 49 people (65.1%). The results of bivariate analysis showed that there was a relationship between carbohydrate intake and nutritional status (p=0.001), there was a relationship between protein intake and nutritional status (p=0.001), while there was no relationship between fat intake and nutritional status of toddlers (p=0.440). Conclusion: There is a relationship between food consumption and the nutritional status of children under five in Carat village in 2024. The intake of carbohydrate, protein, and fat for children under five needs to be increased to support their growth period.